GLOSSARY TO THE JUDGMENT OF THE COURT OF JUSTISE OF THE EUROPEAN UNION C-638/16 X AND X V ÉTAT BELGE - Shulha, Aliaksei (Review of European and Comparative Law, 2017)
The subject of the glossary is to consider certain aspects concerning issuing of humanitarian visas . Its aim is to demonstrate the need for humanitarian visas in order to allow individuals to cross the external borders of the European Union in hopes of protection in one of its Member States . The prohibition of torture, inhuman or degrading treatment derives from the European Union and inter-national law . It confirms the importance of granting international protection to foreigners and accessibility to this procedure . This article is generally based on the Advocate General’s opinion and the judgment of the Court of Justice of the European Union in case C-638/16 X and X v État belge . It is also noted that the Court did not comply with the recommendations of the Advocate General . The arguments used in this article are to show that people in need of international protection should be able to apply for a humanitarian visa under European Union and international law